Three-dimensional ordered porous cerium dioxide as well as preparation method and application thereof

By preparing three-dimensional orderly porous ceria, the problem of low photocatalytic efficiency of traditional ceria is solved, and more efficient photocatalytic performance is achieved. It is suitable for photocatalytic refining agricultural and forestry biomass, cracking water to produce hydrogen and carbon dioxide reduction.

CN119797412APending Publication Date: 2025-04-11NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003202.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The photocatalytic efficiency of traditional ceria is caused by incomplete exposure of active sites and lack of surface oxygen vacancies. In the prior art, the photocatalytic performance of ceria is still relatively poor.

Method used

Using the preparation method of three-dimensional ordered porous ceria, three-dimensional ordered porous ceria with excellent photocatalytic properties is prepared by mixing surfactant, complexing agent, cerium salt and solvent, adding a template agent for impregnation and calcination.

Benefits of technology

The photocatalytic performance of ceria is improved. By adjusting the pore size and pore structure, light can propagate in the three-dimensional ordered porous structure, generate energy band gaps, increase the specific surface area and reactive sites, and improve catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797412A_ABST
    Figure CN119797412A_ABST
Patent Text Reader

Abstract

The invention provides three-dimensional ordered porous cerium dioxide as well as a preparation method and application thereof, and belongs to the technical field of catalysts. In the preparation process, the diameter of the template agent is controlled, the pore diameter and pore structure of the three-dimensional ordered porous cerium dioxide are adjusted, the pore diameter can be matched with light waves with certain wavelength, light can be spread in the three-dimensional ordered porous structure, Bragg diffraction is prevented from being generated, generation of an energy band gap is facilitated, and the preparation method is suitable for large-scale industrial production. And moreover, the gas-solid-liquid contact efficiency in the photocatalytic reaction process can be effectively improved, the specific surface area of cerium dioxide is increased, more reaction active sites are provided, meanwhile, oxygen vacancies are enriched, and the catalytic activity of the cerium dioxide is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a three-dimensional ordered porous cerium dioxide and a preparation method and application thereof. Background Art

[0002] Ceria has unique redox properties, excellent oxygen storage capacity and good chemical stability, and is widely used in photocatalytic reactions, solid oxide fuel cells and carbon monoxide oxidation. However, the photocatalytic efficiency of traditional ceria is still limited by some inherent shortcomings, such as incomplete exposure of active sites and lack of surface oxygen vacancies.

[0003] In order to solve these problems, the morphology of cerium dioxide is adjusted in the prior art to expose the active sites, such as nanoparticles, nanospheres and nanosheet structures. However, the photocatalytic performance of cerium dioxide in the prior art is still poor.

[0004] Therefore, how to further improve the photocatalytic performance of cerium dioxide becomes a difficult problem in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a three-dimensional ordered porous cerium dioxide and a preparation method and application thereof. The three-dimensional ordered porous cerium dioxide prepared by the present invention has excellent photocatalytic performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing three-dimensional ordered porous cerium dioxide, comprising the following steps:

[0008] (1) mixing a surfactant, a complexing agent, a cerium salt and a solvent to obtain a mixed solution;

[0009] (2) impregnating a template in the mixed solution obtained in step (1) and drying the mixture to obtain an intermediate product; the template comprises polymethyl methacrylate or polystyrene; and the diameter of the template is 400 nm to 1 μm;

[0010] (3) calcining the intermediate product obtained in step (2) to obtain three-dimensional ordered porous cerium dioxide.

[0011] Preferably, the surfactant in step (1) comprises at least one of Planck F-127, Planck P123, Pluronic L64 and hexadecyltrimethylammonium bromide.

[0012] Preferably, the complexing agent in step (1) comprises at least one of citric acid, ethylenediaminetetraacetic acid, tartaric acid, oxalic acid and phytic acid.

[0013] Preferably, in step (1), the mass ratio of the surfactant, the complexing agent and the cerium salt is 0.5:1:(1-4).

[0014] Preferably, in step (1), the mass fraction of the cerium salt in the solvent is 1-5%.

[0015] Preferably, the immersion temperature in step (2) is 20 to 30° C., and the immersion time is 2 to 4 hours.

[0016] Preferably, the calcination in step (3) is first carried out in an inert atmosphere and then in an oxygen atmosphere.

[0017] Preferably, in the step (3), the calcination temperature is 300-600° C., the calcination time is 3-5 hours, and the heating rate to the calcination temperature is 1-5° C. / min.

[0018] The present invention also provides three-dimensional ordered porous cerium dioxide prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides the use of the three-dimensional ordered porous cerium dioxide described in the above technical solution in photocatalytic refining of agricultural and forestry biomass, photocatalytic water splitting to produce hydrogen, and photocatalytic carbon dioxide reduction.

[0020] The present invention provides a method for preparing three-dimensional ordered porous cerium dioxide, comprising the following steps: (1) mixing a surfactant, a complexing agent, a cerium salt and a solvent to obtain a mixed solution; (2) impregnating a template in the mixed solution obtained in step (1) and drying the mixture to obtain an intermediate product; the template comprises polymethyl methacrylate or polystyrene; the diameter of the template is 400nm to 1μm; (3) calcining the intermediate product obtained in step (2) to obtain three-dimensional ordered porous cerium dioxide. The present invention controls the diameter of the template, adjusts the pore size and pore structure of the three-dimensional ordered porous cerium dioxide, and the pore size can match a light wave of a certain wavelength. Light can propagate in the three-dimensional ordered porous structure and prevent Bragg diffraction from being generated, which is conducive to the generation of an energy band gap, and can also effectively improve the gas-solid-liquid contact efficiency in the photocatalytic reaction process, increase the specific surface area of ​​cerium dioxide, provide more reactive sites, and enrich oxygen vacancies, thereby improving its catalytic activity. The results of the examples show that the yield of formic acid from corn stalks by photorefining using the three-dimensional ordered porous cerium dioxide prepared by the present invention is 10.7 mmol / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD pattern of the three-dimensional ordered porous cerium dioxide prepared in Example 1 of the present invention;

[0022] Figure 2This is an XPS graph of the three-dimensional ordered porous cerium dioxide prepared in Example 1 of the present invention;

[0023] Figure 3 This is a SEM image of the three-dimensional ordered porous cerium dioxide prepared in Example 1 of the present invention at a magnification of 20,000;

[0024] Figure 4 This is a SEM image of the three-dimensional ordered porous cerium dioxide prepared in Example 1 of the present invention at a magnification of 40,000. DETAILED DESCRIPTION

[0025] The present invention provides a method for preparing three-dimensional ordered porous cerium dioxide, comprising the following steps:

[0026] (1) mixing a surfactant, a complexing agent, a cerium salt and a solvent to obtain a mixed solution;

[0027] (2) impregnating a template in the mixed solution obtained in step (1) and drying the mixture to obtain an intermediate product; the template comprises polymethyl methacrylate or polystyrene; and the diameter of the template is 400 nm to 1 μm;

[0028] (3) calcining the intermediate product obtained in step (2) to obtain three-dimensional ordered porous cerium dioxide.

[0029] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and any commercially available product or product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0030] The invention mixes a surfactant, a complexing agent, a cerium salt and a solvent to obtain a mixed solution.

[0031] In the present invention, the surfactant preferably includes at least one of Planck F-127, Planck P123, Pluronic L64 and hexadecyltrimethylammonium bromide. In the present invention, the surfactant acts as a soft template to subsequently form a porous structure to improve the photocatalytic performance of cerium dioxide.

[0032] In the present invention, the complexing agent preferably includes at least one of citric acid, ethylenediaminetetraacetic acid, tartaric acid, oxalic acid and phytic acid.

[0033] In the present invention, the cerium salt preferably includes cerium nitrate, cerium chloride or cerium sulfate.

[0034] In the present invention, the mass ratio of the surfactant, the complexing agent and the cerium salt is preferably 0.5:1:(1-4). As an embodiment, the mass ratio of the surfactant, the complexing agent and the cerium salt can be 0.5:1:(2-4). The present invention limits the mass ratio of the surfactant, the complexing agent and the cerium salt to the above range, which can further improve the photocatalytic performance of cerium dioxide.

[0035] In the present invention, the solvent is preferably a mixed solution of ethanol and water; the volume ratio of ethanol to water is preferably 1:(0.5-1.5), more preferably 1:1.

[0036] In the present invention, the mass fraction of the cerium salt in the solvent is preferably 1-5%. The present invention limits the composition and amount of the solvent to the above range, so that the raw materials can be fully dissolved.

[0037] The present invention has no special limitation on the mixing operation of the surfactant, complexing agent, cerium salt and solvent. The raw materials can be uniformly mixed using a material mixing technical scheme well known to those skilled in the art.

[0038] After obtaining the mixed solution, the present invention immerses the template in the mixed solution and then dries it to obtain an intermediate product.

[0039] In the present invention, the template comprises polymethyl methacrylate or polystyrene; the diameter of the template is 400 nm to 1 μm.

[0040] In the present invention, the template is preferably prepared by mixing monomers, water and an initiator, performing a polymerization reaction and then filtering to obtain the template.

[0041] In the present invention, the monomer preferably includes methyl methacrylate or styrene.

[0042] In the present invention, the volume ratio of water to monomer is preferably (1-10):1, more preferably (2-10):1.

[0043] In the present invention, the initiator preferably includes potassium persulfate, dibenzoyl peroxide or azobisisobutyronitrile.

[0044] In the present invention, the mass fraction of the initiator to water is preferably 0.5 to 15%, more preferably 1 to 10%.

[0045] In the present invention, the monomer, water and initiator are preferably mixed in the following manner: the monomer and water are uniformly mixed at 50-80° C. in an inert atmosphere and under stirring conditions, and then the initiator is added.

[0046] In the present invention, the inert atmosphere is preferably an argon atmosphere. The present invention has no particular limitation on the mixing time, stirring method and speed, as long as the raw materials are mixed evenly.

[0047] In the present invention, the polymerization reaction temperature is preferably 50-80°C, more preferably 60-80°C; the polymerization reaction time is preferably 80-500 min, more preferably 90-420 min; the polymerization reaction is preferably carried out under stirring conditions; the stirring rate is preferably 100-500 rpm; the polymerization reaction is preferably carried out in an inert atmosphere, more preferably in an argon atmosphere. The present invention limits the polymerization reaction temperature, time, etc. within the above range, so that the polymerization reaction can be fully carried out and the polymer has a suitable diameter.

[0048] In the present invention, the filtration diameter during filtration is 400 nm to 1 μm. The present invention controls the diameter of the template through filtration, thereby obtaining three-dimensional ordered porous cerium dioxide.

[0049] After the filtration is completed, the present invention preferably centrifuges and washes the filtrate obtained by filtration and then dries it to obtain the template.

[0050] The present invention has no special limitation on the operation of the centrifugal washing, and impurities such as unreacted raw materials can be removed by using the centrifugal washing technical scheme well known to those skilled in the art.

[0051] In the present invention, the drying temperature is preferably 20 to 70° C., more preferably 60° C.; the drying time is preferably 10 to 15 hours, more preferably 12 hours.

[0052] In the present invention, the diameter of the template is 400nm to 1μm, preferably 500 to 600nm. The present invention limits the diameter of the template to the above range, which can adjust the pore size and pore structure of the three-dimensional ordered porous cerium dioxide, and its pore size can match a certain wavelength of light. Light can propagate in the three-dimensional ordered porous structure and prevent Bragg diffraction, which is conducive to the generation of a band gap and further improves the photocatalytic performance of cerium dioxide.

[0053] In the present invention, the mass ratio of the template agent to the volume ratio of the mixed solution is preferably (1-5) g:100 mL, more preferably (2-4) g:100 mL. The present invention limits the mass ratio of the template agent to the volume ratio of the mixed solution to the above range, which can further improve the photocatalytic performance of cerium dioxide.

[0054] In the present invention, the impregnation temperature is preferably 20-30°C; the impregnation time is preferably 2-4 hours, more preferably 3 hours; the impregnation is preferably carried out under stirring conditions. The present invention has no special restrictions on the stirring method and rate, and the stirring method and rate familiar to those skilled in the art can be used. The present invention limits the impregnation temperature and time to the above range, and can contain more templates, further improving the photocatalytic performance of cerium dioxide.

[0055] In the present invention, the drying temperature is preferably 50 to 70° C., more preferably 60° C.; the drying time is preferably 8 to 12 hours.

[0056] After obtaining the intermediate product, the present invention calcines the intermediate product to obtain three-dimensional ordered porous cerium dioxide.

[0057] In the present invention, the calcination temperature is preferably 300-600°C, more preferably 400-600°C; the calcination time is preferably 3-5h, more preferably 4h; the heating rate to the calcination temperature is preferably 1-5°C / min. In an embodiment of the present invention, the heating rate to the calcination temperature can be specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0058] In the present invention, the calcination is preferably first calcined in an inert atmosphere and then calcined in an oxygen atmosphere, more preferably first calcined in a nitrogen atmosphere for 0.5 to 1.5 hours and then calcined in an oxygen atmosphere for 2.5 to 3.5 hours. The present invention first carbonizes the template in an inert atmosphere and then removes it by oxidation in an oxygen atmosphere. The calcination method of the present invention and controlling the calcination temperature, time and heating rate can further improve the photocatalytic performance of cerium dioxide.

[0059] After the calcination is completed, the present invention preferably cools the calcined product to obtain three-dimensional ordered porous cerium dioxide.

[0060] In the present invention, the cooling is preferably natural cooling.

[0061] The present invention controls the diameter and amount of the template agent during the preparation process, adjusts the pore size and pore structure of the three-dimensional ordered porous cerium dioxide, and improves the photocatalytic performance of the cerium dioxide.

[0062] The present invention also provides three-dimensional ordered porous cerium dioxide prepared by the preparation method described in the above technical solution.

[0063] In the present invention, the pore size of the three-dimensional ordered porous ceria is preferably 200 to 400 nm.

[0064] The present invention also provides the use of the three-dimensional ordered porous cerium dioxide described in the above technical solution in photocatalytic refining of agricultural and forestry biomass, photocatalytic water splitting to produce hydrogen, and photocatalytic carbon dioxide reduction.

[0065] In the present invention, the agricultural and forestry biomass is preferably corn stover.

[0066] In the present invention, the application of the three-dimensional ordered porous cerium dioxide in photocatalytic refining of corn stalks is preferably:

[0067] In a reactor with a quartz window on the top, three-dimensional ordered porous cerium dioxide, corn stalks and sodium hydroxide aqueous solution are mixed to obtain a mixed solution; oxygen is injected into the reactor to raise the pressure in the reactor to 0.9-1 MPa; a 300W xenon lamp is used as a light source with a light source intensity of 140-160mW / cm -2 , the products were analyzed by gas chromatography and flame ionization detector to obtain the yield of corn stover cellulose converted to formic acid.

[0068] In the present invention, the mass ratio of the three-dimensional ordered porous cerium dioxide to corn straw is preferably (0.1-0.3):1, and more preferably 0.2:1.

[0069] In the present invention, the mass concentration of the sodium hydroxide aqueous solution is preferably 3-5%, more preferably 4%; the mass ratio of the three-dimensional ordered porous cerium dioxide to the sodium hydroxide aqueous solution is preferably 20:(25-100).

[0070] The invention adopts three-dimensional ordered porous cerium dioxide as a photocatalyst with excellent photocatalytic performance, and improves the yield of converting corn straw cellulose into formic acid in the process of photocatalytic corn straw light refining.

[0071] The present invention has no special limitation on the operation of using the three-dimensional ordered porous cerium dioxide in photocatalytic water splitting to produce hydrogen and photocatalytic carbon dioxide reduction, and the technical solutions well known to those skilled in the art can be adopted.

[0072] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0073] Example 1

[0074] The preparation method of three-dimensional ordered porous cerium dioxide is:

[0075] (1) deionized water and methyl methacrylate in a volume ratio of 2:1 were stirred uniformly at 80° C. in an argon atmosphere, 0.3 g of potassium persulfate (the mass fraction of potassium persulfate in water was 1%) was quickly added, and a polymerization reaction was carried out at 80° C. at a stirring rate of 400 rpm for 90 min to obtain a crude product, the crude product was filtered with filter paper, the filtrate was centrifuged and washed, and dried at 60° C. for 12 h to obtain polymethyl methacrylate, the diameter of the polymethyl methacrylate being 500 nm to 1 μm;

[0076] (2) Planck F-127, citric acid and cerium nitrate in a mass ratio of 0.5:1:2.5 were stirred and dissolved in 100 mL of a mixed solvent of ethanol / deionized water in a volume ratio of 1:1 (the mass fraction of cerium nitrate in the solvent was 2.5%) to obtain a mixed solution;

[0077] (3) adding 2 g of the polymethyl methacrylate obtained in step (1) to the mixed solution of step (2), stirring and impregnating at room temperature for 3 h, and drying in an oven at 60 ° C for 12 h to obtain an intermediate product;

[0078] (4) The intermediate product obtained in step (3) is transferred to a porcelain boat, placed in a tubular calcining furnace, and calcined in a nitrogen atmosphere for 1 h at 600 ° C and a heating rate of 2 ° C / min, and then calcined in an oxygen atmosphere for 3 h. The product is naturally cooled to room temperature to obtain a three-dimensional ordered porous cerium dioxide.

[0079] Example 2

[0080] (1) 0.235 mol of styrene, 0.33 mmol of potassium persulfate and 240 mL of deionized water were stirred uniformly at 70° C. under an argon atmosphere, and a polymerization reaction was carried out at a stirring rate of 300 rpm for 7 hours to obtain a crude product. The crude product was filtered with filter paper, the filtrate was centrifuged and washed, and dried at room temperature for 12 hours to obtain polystyrene, and the diameter of the polystyrene was 400 to 600 nm;

[0081] (2) Planck F-127, citric acid and cerium nitrate in a mass ratio of 0.5:1:2.5 were stirred and dissolved in 100 mL of a mixed solvent of ethanol / deionized water in a volume ratio of 1:1 (the mass fraction of cerium nitrate in the solvent was 2.5%) to obtain a mixed solution;

[0082] (3) adding 2 g of the polystyrene obtained in step (1) to the mixed solution of step (2), stirring and impregnating at room temperature for 3 h, and drying in an oven at 60° C. for 12 h to obtain an intermediate product;

[0083] (4) The intermediate product obtained in step (3) is transferred to a porcelain boat, placed in a tubular calcining furnace, and calcined in a nitrogen atmosphere for 1 h at 600 ° C and a heating rate of 2 ° C / min, and then calcined in an oxygen atmosphere for 3 h. The product is naturally cooled to room temperature to obtain a three-dimensional ordered porous cerium dioxide.

[0084] Comparative Example 1

[0085] The filtration in step (1) of Example 1 was omitted, and other parameters were the same as those of Example 1.

[0086] Comparative Example 2

[0087] The mass ratio of Planck F-127, citric acid and cerium nitrate in step (2) of Example 1 was replaced with 0.5:1:5, and the other parameters were the same as those in Example 1.

[0088] Comparative Example 3

[0089] The heating rate in step (4) of Example 1 was replaced with 10°C / min, and the other parameters were the same as those of Example 1.

[0090] Comparative Example 4

[0091] The diameter of the polymethyl methacrylate in step (1) of Example 1 is replaced with 100-200 nm, and the other parameters are the same as those of Example 1.

[0092] The XRD pattern of the three-dimensional ordered porous cerium dioxide prepared in Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the peak at 28.4° corresponds to the (111) crystal plane of ceria, the peak at 33.1° corresponds to the (200) crystal plane of ceria, the peak at 47.5° corresponds to the (220) crystal plane of ceria, and the peak at 56.4° corresponds to the (311) crystal plane of ceria, which corresponds well to the standard card PDF#34-0394, indicating that the three-dimensional ordered porous ceria photocatalytic material was successfully synthesized.

[0093] The XPS image of the three-dimensional ordered porous cerium dioxide prepared in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the peak at 529.0 eV corresponds to O 2- , the peak at 531.4 eV corresponds to O2 2- , the peak at 532.8 eV corresponds to O 2- , which can explain the existence of active oxygen vacancies on the surface of three-dimensional ordered porous ceria photocatalytic materials.

[0094] The cerium dioxide prepared in Example 1 was observed using a scanning electron microscope, and the SEM images obtained at magnifications of 20,000 and 40,000 were as follows: Figures 3-4 As shown. Figures 3-4 It can be seen that the three-dimensional ordered porous cerium dioxide presents a honeycomb-like structure with an average pore size of about 250 nm.

[0095] The BET characterization of the cerium dioxide prepared in Example 1 revealed that the specific surface area of ​​the three-dimensional ordered porous cerium dioxide was 66.94 m 2 / g.

[0096] Scanning electron microscope was used to observe the cerium dioxide prepared in Comparative Examples 1 to 3, and it can be seen that the cerium dioxide in Comparative Example 1 presents a disordered structure with different particle sizes; the CeO2 in Comparative Example 2 partially presents a honeycomb-like structure and partially presents a disordered structure, which is because the excessive cerium nitrate leads to the inability to completely impregnate the three-dimensionally ordered polymethyl methacrylate; the CeO2 in Comparative Example 3 does not have a three-dimensional ordered porous structure, which is because the heating rate is too fast, resulting in rapid removal of polymethyl methacrylate, and the morphological characteristics of the original template cannot be maintained.

[0097] The three-dimensional ordered porous cerium dioxide prepared in Example 1 was used as a photocatalyst for photorefining of corn stalks. The specific process was as follows: in a reactor with a quartz window on the top, 20 mg of photocatalyst, corn stalks and a 4 wt % sodium hydroxide aqueous solution were stirred and mixed to obtain a mixed solution; oxygen was injected into the reactor to raise the pressure in the reactor to 1 MPa; the mass ratio of the photocatalyst to the corn stalks was 0.2:1, and the mass ratio of the photocatalyst to the sodium hydroxide aqueous solution was 20:50; a 300 W xenon lamp was used as a light source, and the light source intensity was 150 mW / cm -2 The product was analyzed by gas chromatography and flame ionization detector, and the yield of corn straw cellulose converted to formic acid was 10.7 mmol / L. Under the same steps, the yield of formic acid converted from the honeycomb-like CeO2 photocatalytic refining corn straw cellulose obtained in Comparative Example 4 was 2.9 mmol / L, which may be due to the small pore size and inability to fully contact with the corn straw cellulose.

[0098] In summary, the three-dimensional ordered porous cerium dioxide prepared by the present invention has excellent photocatalytic performance.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing three-dimensional ordered porous cerium dioxide, comprising the following steps: (1) mixing a surfactant, a complexing agent, a cerium salt and a solvent to obtain a mixed solution; (2) impregnating a template in the mixed solution obtained in step (1) and drying the mixture to obtain an intermediate product; the template comprises polymethyl methacrylate or polystyrene; and the diameter of the template is 400 nm to 1 μm; (3) calcining the intermediate product obtained in step (2) to obtain three-dimensional ordered porous cerium dioxide.

2. The preparation method according to claim 1, characterized in that: The surfactant in step (1) includes at least one of Planck F-127, Planck P123, Pluronic L64 and hexadecyltrimethylammonium bromide.

3. The preparation method according to claim 1, characterized in that: The complexing agent in step (1) includes at least one of citric acid, ethylenediaminetetraacetic acid, tartaric acid, oxalic acid and phytic acid.

4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the surfactant, the complexing agent and the cerium salt is 0.5:1:(1-4).

5. The preparation method according to claim 1, characterized in that: In the step (1), the mass fraction of the cerium salt in the solvent is 1-5%.

6. The preparation method according to claim 1, characterized in that: The immersion temperature in step (2) is 20 to 30° C., and the immersion time is 2 to 4 hours.

7. The preparation method according to claim 1, characterized in that: The calcination in step (3) is first carried out in an inert atmosphere and then in an oxygen atmosphere.

8. The preparation method according to claim 1, characterized in that: In the step (3), the calcination temperature is 300-600° C., the calcination time is 3-5 hours, and the heating rate to the calcination temperature is 1-5° C. / min.

9. The three-dimensional ordered porous cerium dioxide prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional ordered porous cerium dioxide as described in claim 9 in photocatalytic refining of agricultural and forestry biomass, photocatalytic water splitting to produce hydrogen, and photocatalytic carbon dioxide reduction.